THE PERSPECTIVES OF PHYSICAL EDUCATION AND SPORT IN MOUNTAINOUS BANAT - Zuiac Silvia Sorina; Ghitescu Roxana Emanuela (Sport şi Societate)
In Romania, sports policy is not the monopoly of a single state authority, nor provided for by a single legislative act, in addition to the incidence of national and European institutions and legislative acts, also witnessing a process of decentralization at national level of political, administrative and financial decision making. Both the Government and the local public authorities, in this case the county council, can promote strategies and measures in investing public money in prevention policies for a healthier population. Strategies meant to fit into the logic of such an approach in the field of sports, to contribute to improving the health and quality of life of the citizens of Timiș County by increasing participation in sports activities to prevent, not to treat. In the context of the above, corroborated with other aspects, they are intended to bring into focus the need and the obligation to develop a medium- and long-term strategy in terms of physical education and sport. Therefore, studying and analyzing the perspectives of this field in the mountainous area of Banat represents a challenge for any specialist. In the conditions of globalization, sport represents an environment with strong potential for the affirmation of national identity. Each country of the European Union has its own tradition and culture, which can also be defined by the characteristics of sport. At the level of Caras – Severin County there is a strategy that is the basis for ensuring the necessary support for carrying out the physical education and sports activities at the level of the current international requirements. Even in the current socio-economic context, including through the European funds allocated for this purpose, there are favorable premises for the development of physical education and sport.